Comparative Phytochemicals Screening, Antibacterial and Antioxidant Properties of Some Selected Medicinal Plants in Nigeria - Danjuma, Kabir (CV Media Inti Teknologi, 2025)
Background: Antibiotics resistance poses serious health threats globally, necessitating the search and development of an efficient environmentally friendly antibiotics. Evaluation of medicinal plants possessing antioxidant and antimicrobial chemicals is essential for solving this problem and improves human health.Aims: This research was done to assess the phytochemical status, antioxidant and antibacterial potentials of the leaf extracts of four medicinal plants (Moringa oleifera, Linus usitatissimum, Vernonia amygdalina, and Anacardium occidentale) cultivated in Nigeria. Methods: Standard methods were used to screen the phytochemicals; agar well diffusion and DPPH radical scavenging assays were employed to evaluate the antibacterial and antioxidant properties of the extracts. Results: The results showed that the medicinal plants tested possessed significant phytochemicals including alkaloids, flavonoids, phenolics, terpenoids, tannins, saponins, among others. The plants showed effective antibacterial properties, with Moringa oleifera showing highest antibacterial activities against Staphylococcus aureus and Escherichia coli, followed by Vernonia amygdalina, Linus usitatissimum, and anacardium occidentale. The medicinal plants also showed powerful antioxidant potentials with lower IC50 values. moringa oleifera being the most powerful has an IC50 value of 41.95 µg/ml, followed by Linus usitatissimum (IC50 = 43.09 µg/ml), Vernonia amygdalina (IC50 = 54.64 µg/ml), and anacardium occidentale (IC50 = 66.85 µg/ml), compared with the standard ascorbic acid (IC50 = 14.14 µg/ml)). Conclusion: The medicinal plants tested in this study possess significant bioactive compounds and could serve as an effective potential agent against pathogenic bacteria, suppress oxidative stress thereby improving the human health quality.